Patients with inflammatory myopathies overlapping with systemic sclerosis: A Brazilian-Japanese bicentric study - Jucier Gonçalves Júnior; Naoki Mugii; Pleiades Tiharu Inaoka; Renata Miossi; Fernando Henrique Carlos De Souza; João Calvino Soares De Oliveira; Fujiko Someya; Yasuhito Hamaguchi; Takashi Matsushita; Percival Degrava Sampaio-Barros; et al. (Archives of Rheumatology, 2023)
Objectives: This study aims to describe and compare the demographic, clinical, and laboratory characteristics and follow-up of representative samples of patients with myopathies and systemic sclerosis overlap syndromes (Myo-SSc) from two tertiary centers. Patients and methods: This is a cross-sectional and retrospective study conducted between January 2000 and December 2020. Fourty-five patients were analyzed with Myo-SSc (6 males, 39 females; mean age: 50.2±15.4 years; range, 45 to 65 years) from two tertiary centers (n=30 from Brazil and n=15 from Japan). Results: The median follow-up was 98 (range, 37 to 168) months. Muscle impairment started simultaneously with the diagnosis of systemic sclerosis in 57.8% (26/45) of cases. Muscle involvement occurred before the onset of systemic sclerosis in 35.5% (16/45) of cases, and after in 6.7% (3/45). Polymyositis was observed in 55.6% (25/45) of cases, followed by dermatomyositis in 24.4% (11/45) and antisynthetase syndrome in 20.0% (9/45). Concerning systemic sclerosis, the diffuse and limited forms occurred in 64.4% (29/45) and 35.6% (16/45) of the cases, respectively. Comparing the subgroups, Myo or SSc onset was earlier in Brazilian patients, and they had a higher frequency of dysphagia (20/45, [66.7%]) and digital ulcers (27/45, [90%]), whereas Japanese patients had higher modified Rodnan skin scores (15 [9 to 23]) and prevalence of positive anti-centromere antibodies (4/15 [23.7%]). The current disease status and mortality were similar in both groups. Conclusion: In the present study, Myo-SSc affected middle-aged women, and its manifestation spectrum varied according to geographic distribution.